Significance: U.S. Blind Spots in Judging Research - Anderson-Levitt, Kathryn M. (Education Policy Analysis Archives, 2014)
Opening U.S. educational publishing to the rest of the world promises fresh perspectives and new solutions—but not if U.S.-based editors, reviewers and readers fail to recognize the significance of research conducted outside the United States. This essay explores why U.S.-based reviewers easily miss the social importance and the intellectual interest of research conducted elsewhere, and points to several steps they can take to improve their appreciation of the full global range of educational scholarship.